Carpal Tunnel Syndrome Caused by Gout: Clinical Presentations, Surgical Findings, and Outcomes After Surgery - Kwok-Chu Joseph Mak; Fu-Keung Ip; Tak-Chuen Wong; Siu-Ho Wan; Sze-Yan Chan (Journal of Orthopaedics, Trauma and Rehabilitation, 2015)
Background/Purpose: Carpal tunnel syndrome caused by gout is rare. We presented our experience in treating these patients. Methods: We conducted a retrospective review of cases treated from 2010 to 2013. Eight patients were identified out of 348 carpal tunnel releases performed. Results: All patients were male. All patients had gouty tophi on the same hand and other locations on the body. Open carpal tunnel release was performed on all patients. There was gouty tenosynovitis in all patients but no encasement of the median nerve. The mean follow-up was 16 months. Numbness improved in seven out of eight patients. Conclusion: Gout should be considered a cause of carpal tunnel syndrome, particularly in patient with a history of gout. Early surgical outcome is promising. Longer follow-up is needed to detect recurrence.